Desain Alat Ukur Kadar Asam Urat Non-Invasive Dengan Sensor Near Infrared - Umar, Usman; Hasmah, Hasmah; Alyah, Risnawaty; Syam, Anita Nur (Lontara Journal of Health Science and Technology, 2021)
Gout disease or commonly known as gout arthritis is a disease caused by the accumulation of monosodium urate crystals in the body. Monitoring blood uric acid levels is currently still using invasive techniques by taking blood samples to be included in the test strip, this invasive technique measurement requires money and time to come to health clinics so that many people cannot monitor blood uric acid levels on a regular basis. This study aims to develop a measuring instrument for monitoring blood uric acid levels using sensors by utilizing the absorption and reflectance of infrared rays so that gout sufferers and other individuals can monitor blood uric acid levels regularly and are easy to use. The method of developing non-invasive techniques focuses on monitoring blood uric acid levels using a NIR sensor with an IR LED with a wavelength of 940 nm as a transmitter and a photodiode as a detector at a wavelength of 700-1300 nm and a microcontroller as a minimum system for control. The first stage is measuring uric acid levels with invasive techniques on participants and at the same time measuring voltages with sensors, the results with invasive techniques are correlated with sensor output voltages to obtain non-linear equations in polynomial form, for conversion programs on the microcontroller. The second stage is measuring uric acid levels with invasive techniques and invasive measurements on participants at the same time. Both monitoring results were analyzed by simple ANOVA statistics and calculated SEP and RMSE to determine the accuracy of the prediction equation and its accuracy value.